Calorie restriction regime enhances physical performance of trained athletes. Issue 1 (9th March 2018) - Pons, Victoria; Riera, Joan; Capó, Xavier; Martorell, Miquel; Sureda, Antoni; Tur, Josep A.; Drobnic, Franchek; Pons, Antoni
Abstract: Background: Caloric restriction induces mitochondrial biogenesis and improves physical fitness in rodents. We aimed to provide evidence of how caloric restriction affects the body composition and physical performance of trained athletes and to evaluate the possible impact of an every-other-day feeding diet on nutritional deficiencies of micronutrients and essential fatty acids. Methods: The study was performed with 12 healthy male athletes by carrying out a 33% caloric restriction with respect to their usual diet. Athletes performed a maximal exercise stress test both before and after the caloric restriction period. Blood samples were taken before and after the caloric restriction at basal conditions and 30 min post-exercise. Although energy intake was reduced by about 33%, the contribution of carbohydrates, proteins, and lipids to total energy intake during the caloric restriction was similar to the original diet. Results: The caloric restriction reduced the daily specific micronutrient intake to values lower than 90% of recommended dietary allowances. No effects were observed in blood parameters related to iron metabolism and tissue damage, glucose levels, lipid profiles, or erythrocyte fatty acid composition. In addition, oxidative damage markers decreased after the nutritional intervention. The caloric restriction intervention significantly reduced body weight and trunk, arm, and leg weights; it also caused a decrease in fat and lean body mass, the energy expenditure rate when performing a maximal exercise stress test, and the energy cost to run one meter at various exercise intensities. Furthermore, the intervention ameliorated the onset of the anaerobic phase of exercise. Conclusion: A caloric restriction improves athletes' performance and energy efficiency, but reduces the daily intake of micronutrients; so, when caloric restriction programs are implemented micronutrient supplementation should be considered. Trial registration: The project was registered at ClinicalTrials.gov (NCT02533479).